Pemetaan Tren dan Arah Riset Rantai Nilai Kopi: Bibliometric And Content Analysis - Suprehatin Suprehatin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
As one of the Indonesia's strategic commodities and a key commodity for global trade, coffee continues to be an interesting and growing topic for research. This study aims to identify the development of literature and scientific mapping in coffee value chain studies and its implications for future coffee value chain research in Indonesia. This study uses secondary data in the form of journal articles related to the agrifood value chain in coffee commodities as many as 264 documents obtained from the Scopus database per March 2025. The data were analyzed using bibliometric and content analysis. The results showed that coffee value chain research topics were divided into five clusters: (1) global value chain and certification, (2) coffee farmers and value addition, (3) social and gender issues in coffee farming, (4) arabica coffee and environmental sustainability, and (5) fair trade and circular economy in coffee. The results also show that the current trend of coffee value chain research is developing towards a more holistic coffee value chain development that includes economic, social, and environmental dimensions and is multidisciplinary. The results provide insights into research gaps in the Indonesian context and offer new research opportunities and areas for future coffee value chain.